Early vestibular rehabilitation training of peripheral acute vestibular syndrome—a systematic review and meta-analysis - Agger-Nielsen, Helle Elisabeth; Grøndberg, Thomas Stig; Berg-Beckhoff, Gabriele; Ovesen, Therese (Frontiers in Neurology, 2024)
Objective This study aimed to investigate the impact of early vestibular rehabilitation training combined with corticosteroids initiated within 2 weeks, compared with corticosteroid treatment, after the peripheral acute vestibular syndrome (pAVS) onset. Data sources PubMed, CINAHL, EMBASE, and SCOPUS. From inception to January 24, 2024. The International Prospective Register of Systematic Reviews approved this study (CRD42023422308). Results Five studies involving 235 patients were included in this systematic review and meta-analysis. The subjective outcome measure Dizziness Handicap Inventory (DHI) was pooled for a meta-analysis and was statistically significantly in favor of early vestibular rehabilitation training (early VRT) plus corticosteroids compared with corticosteroids alone: at one-month follow-up (p = 0.00) and 12 months follow-up (p = 0.01). DHI was a critical outcome for measuring the differences in effect of early VRT. The objective outcome measures of caloric lateralization, cervical vestibular-evoked myogenic potentials, and posturography were gathered for a narrative synthesis. Conclusion This meta-analysis showed that early VRT in combination with corticosteroids was more effective for treating pAVS than corticosteroid treatment alone. No adverse effects were reported for early VRT.